Menghitung Besar Biaya (Cost) Dari Perancangan Perawatan Menggunakan Metode Reliability Centered Maintenance Pada Fuel Boost Pump Pesawat Boeing 737-400 - Octaline Putri Efma; Reo Yudhono; Arfie Armelia Erissonia; Ferry Setiawan (Jurnal Mahasiswa Kreatif, 2023)
This study aims to know the cost of designing maintenance using the Reliability Centered Maintenance method. Engine and fuel control, is a fuel engine system and fuel control system; in charge of distributing and measuring fuel from the fuel storage tank, to the combustion chamber. Gas turbine or component area (Combustor), functions as a distributor of fuel used in aircraft systems and plays a role in carrying out its operation (Boeing 737-400 Aircraft Maintenance Manual). Reliability is the possibility of a component or system to be able to operate and/or carry out its functions. The function has been assigned to certain operating conditions and in a certain environment for a predetermined period of time. Thus, reliability is the probability that it will not fail or be able to perform its function for a period of time (t) or more. In the analysis of preventive maintenance financing, which is carried out when the reliability value reaches 70%, 60% and 50%, respectively, it is obtained for each component.